New environmentally friendly catalysts containing Pd-interstitial carbon made from Pd-glucose precursors for ultraselective hydrogenations in the liquid phase. - Chan, C; Xie, Y; Cailuo, N; Yu, K; Cookson, J; Bishop, P; Tsang, S (2011)
We report a novel preparation of a Pd nanocatalyst modified with subsurface C via blending a glucose precursor at the molecular level: the catalyst is demonstrated for the first time to be stereoselective in the hydrogenation of alkynes to cis-alkenes in the liquid phase.